Pengaruh Penggunaan Multimedia Pembelajaran 3D Pageflip Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Wirausaha Kelas VII SMP Laboratorium STKIP Kota Jambi - Zanjani, Ahmad; Sembiring, Benar (SJEE (Scientific Journals of Economic Education), 2024)
This research aims to determine the learning outcomes of students who use or do not use 3D Pagflip in entrepreneurship subjects during the post-test using 3D Pageflip. This type of research uses experiments. The research results show that there is a comparison of learning outcomes between students who use 3D Pageflip and those who do not use 3D Pageflip. It can be seen that the experimental class obtained a higher passing score than the control class, besides that it can be calculated with an average score of 1.05. Thus, using 3D Pageflip can help students be more creative and focused in improving student learning outcomes.